Cytokines pre-determined by genetic factors are involved in pathogenesis of Rheumatoid arthritis. Issue 2 (October 2015) - Taneja, Veena
Highlights HLA alleles positively select T cells and predetermine production of TH17/TH2 under different conditions. HLA alleles that produce TH1/TH17 cytokines and provide advantage in clearing infections have been preserved for generations. Most studies point a significant role of molecular mimicry in autoimmunity.